CONTINUITY OF CARE FOR MRS. A WITH PERINEAL RUPTURE DEGREE II AT PMB RIMENDA TARIGAN, MEDAN DENAI DISTRICT, NORTH SUMATRA PROVINCE, MEDAN CITY IN 2025 - Sihombing, Putri Aprilia; Kamelia Sinaga; Rimenda Tarigan; Septiani Chintiya; Dwi Agustina; Desi Handayani; Risna Meliana Rumahorbo (Mitra Husada Health Internasional Conference (MIHHICo), 2026)
According to WHO (World Health Organization) data, AKI is still very high with an average number of 295,000 women dying during pregnancy and childbirth, in 2018 the ASIAN country with the most AKI is Laos with the highest number of AKI 197 per 100,000 and AKI which is 20 per 1000 live births while when compared to Indonesia in 2021 it reached 2,982 people with an AKI of 305 per 100,000 live births and in North Sumatra in 2021 the AKI reached 119 cases and AKB 299 cases. Continuity of Care (COC) is an effort to help monitor and identify possible complications that accompany the mother and baby from pregnancy to the use of contraceptives by the mother. Purpose: Providing obstetric care services on a Continuity of Care (COC) basis starting from pregnancy, childbirth, postpartum period, newborn care, and family planning. Method: The method used for comprehensive treatment for Mrs. A is descriptive research, which systematically describes the phenomenon based on the type used, i.e. case studies. Result: Checking the completeness of the placenta and the presence of a rupture of the second degree birth canal (from the vaginal mucosa, posterior commissura of the perineal skin to the perineal muscle) and the placenta was born complete with a length of the umbilical cord of 50 cm, the number of cotyledons 19, and a diameter of 20 cm. Conclusion: Helps understand the pregnancy process to family planning. In Mrs. A, when the third trimester of pregnancy begins in November 2024 to Mare 2025, the author conducts COC guidance with the aim of successful Continuity of Care treatment(WHO, 2023)(Yoki Foranci, 2023)(Lapau, 2021)(Naohiro Yonemoto, 2023)